New Training Strategies and Evaluation Methods for Improving Health and Physical Performance - Matias, Catarina Nunes; Toselli, Stefania; Monteiro, Cristina; Campa, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this Special Issue was to propose, on the basis of the evidence that the current literature provides, new training techniques and specific evaluation methods for the different populations practicing physical activity.